Immunoglobulin G4 비관련 특발성 경화성 장간막염 - 권태형; Tae Hyung Kwon; 조광범; Kwang Bum Cho; 이현직; Hyun Jik Lee; 권선영; Sun Young Kwon; 이윤석; Yoon Suk Lee (The Korean journal of gastroenterology, 2019)
Sclerosing mesenteritis is a rare benign disease with a prevalence of 0.16-3.4% and is characterized by chronic nonspecific inflammation and extensive fibrosis in the adipose tissue of the mesentery although the exact pathogenesis is still elusive. A 65-year-old woman was referred with suspicion of an abdominal mass and biliary stones on abdominal ultrasonography and CT. Bile duct stones were confirmed by endoscopic ultrasonography and successfully treated by endoscopic retrograde cholangiography with stone removal. Furthermore, a 4.7 cm conglomerated mass on small intestinal mesentery was suspected as sclerosing mesenteritis based on the features on abdominal MRI. However, because it could not be differentiated from malignancy without histologic examination, laparoscopic excisional biopsy was performed; it showed only inflammatory cells with extensive fibrosis. Therefore, the abdominal mass was confirmed as sclerosing fibrosis and the patient was followed-up without any treatments because no mass-related symptoms accompanied the findings. Six months later, abdominal CT showed no significant change in the mass. Herein, we report a rare case of incidentally found idiopathic sclerosing mesenteritis. (Korean J Gastroenterol 2019;73:50-55)